2019
DOI: 10.1007/s13202-019-0696-8
|View full text |Cite
|
Sign up to set email alerts
|

The associative polymer flooding: an experimental study

Abstract: This study investigates the sandpack displacement of low viscosity oil (1.68 cP) by brine and aqueous solutions of associative polymers. Polymer flooding has been thoroughly investigated in many laboratory and field tests. Polymer flooding is one of the most widely used enhanced oil recovery (EOR) methods. The method of polymer flooding is not used for development of oil fields with gas caps, fractured reservoirs, high permeability and active bottom-water drive. In the application of polymer flooding, coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Associative polymers are structured in a way that the backbone of the polymer is attached to both hydrophobic and hydrophilic moieties. 47 Molecules/intermolecular associations form an amphiphilic structure, thereby enhancing the fluid performance in high-salinity reservoirs.…”
Section: Polymers In Fracturing Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associative polymers are structured in a way that the backbone of the polymer is attached to both hydrophobic and hydrophilic moieties. 47 Molecules/intermolecular associations form an amphiphilic structure, thereby enhancing the fluid performance in high-salinity reservoirs.…”
Section: Polymers In Fracturing Fluidsmentioning
confidence: 99%
“…Moreover, in the recent literature, interesting results were reported from hydrophobically modified polymers (associative polymers), which can offer a great tolerance at higher salinities. Associative polymers are structured in a way that the backbone of the polymer is attached to both hydrophobic and hydrophilic moieties . Molecules/intermolecular associations form an amphiphilic structure, thereby enhancing the fluid performance in high-salinity reservoirs.…”
Section: Polymers In Fracturing Fluidsmentioning
confidence: 99%
“…Similar studies were also performed by Zhang et al (2019), who noted that the injection of HMAP in porous media increased the oil recovery factor by 18.7% compared to PHPA injection. Abirov et al (2019) performed porous media tests with commercial PHPA and HMAP solutions simulating conditions of the Turgay Southern Basin reservoir in Kazakhstan, where severe salinity and temperature conditions prevail (92 000 ppm TDS and 82°C). They reported that the associative polymer was more stable and efficient in the simulated reservoir conditions and recommended its pilot scale application.…”
Section: Hydrophobically Modified Associative Polymers (Hmaps)mentioning
confidence: 99%
“…Associative polymers are hydrophilic macromolecular chains with hydrophobic groups, the content of which is generally 2–5 mol%. Hydrophobic groups on the molecular chain cooperate with the electrostatic repulsion and attraction of charged-ion groups to make macromolecular chains produce intramolecular or intermolecular associations, combine to form independent aggregates, and form various supramolecular spatial network structures [ 11 , 12 , 13 ]. After the “dynamic physical glue network structure” formed by hydrophobic association is destroyed by external forces, this structure reassociates and restores part of the spatial structure [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%